2020
DOI: 10.1002/hbe2.183
|View full text |Cite
|
Sign up to set email alerts
|

The ethics of studying digital contexts: Reflections from three empirical case studies

Abstract: The purpose of this article is to highlight important research-related ethical issues and provide researchers with guiding questions for producing ethical research of digital contexts. We also suggest that research ethics can be understood as a bridge between the seemingly distinct subfields across digital media studies. The article discusses three empirical case studies that reflect three main subfields and three research methodologies-ethnography and cultural media studies, critical discourse analysis and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Cyberethnography is a qualitative-interpretive approach to studying social interactions and cultures manifested and experienced through internet-based media (Yadlin-Segal et al, 2020). This approach is neither solely focused on the media nor on the agentic subjects using them, and acknowledges that media are inseparable from the other activities, technologies, materialities, and feelings through which they are used, experienced, and operated (Pink et al, 2015).…”
Section: Methods Data and The Research Contextmentioning
confidence: 99%
“…Cyberethnography is a qualitative-interpretive approach to studying social interactions and cultures manifested and experienced through internet-based media (Yadlin-Segal et al, 2020). This approach is neither solely focused on the media nor on the agentic subjects using them, and acknowledges that media are inseparable from the other activities, technologies, materialities, and feelings through which they are used, experienced, and operated (Pink et al, 2015).…”
Section: Methods Data and The Research Contextmentioning
confidence: 99%
“…The majority of papers (n = 13) concurred that consent was more ambiguous in public online spaces [8,11] and was an ongoing process requiring continual reflection and communication with participants [4,18,19,23,25,27,30,32,33,35,36,[38][39][40]. Eight papers repeated the BPS assertion that not seeking consent for public domain online data could be justified when the scientific and social value outweighed the associated risk [18,19,23,30,33,36,38,40].…”
Section: Plos Onementioning
confidence: 99%
“…In line with AoIR, seven papers gave attention to the expectations of online communities in relation to research [19,25,30,33,36,39,40]. For example, Burles et al [25] suggested that disrupting online illness support communities could cause members to change or reduce the support they provide to others.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Discussions that occur in public online spaces are easily searchable. Even when participants provide consent, they may not fully connect consent to the analysis and public sharing of all their interactions over time in an online space (Yadlin-Segal et al, 2020). Although relatively few people may be able to identify individuals from these transcripts, instructors and students who were class members may either recall specific conversations or be able to revisit course archives and search for them.…”
Section: Research Approaches and Focimentioning
confidence: 99%